Dietary net energy levels for growing barrows from 30 to 70 kg - Gabriela Puhl Rodrigues; Charles Kiefer; Karina Márcia Ribeiro de Souza Nascimento; Anderson Corassa; Danilo Alves Marçal; Marina de Nadai Bonin; Alexandre Pereira dos Santos; Luana Cristiane dos Santos (Ciência Rural, 2021)
ABSTRACT: This study evaluated the effect of dietary net energy (NE) levels on growth performance and carcass characteristics of barrows from 30 to 70 kg of body weight (BW). Sixty barrows with initial body weight (IBW) of 31.94 ± 3.54 kg and final body weight (FBW) of 71.98 ± 5.99 kg were allotted to one of five dietary NE levels (2.40, 2.45, 2.50, 2.55, and 2.60 Mcal kg-1), using a completely randomized block design with six replicates and two barrows per replicate. The experimental period was divided into phase I: 30 to 50 kg and phase II: 50 to 70 kg. The variables analyzed were average daily feed intake (ADFI), net energy intake (NEI), digestible lysine intake (LysI), average daily gain (ADG), feed conversion (FC), FBW, digestible lysine conversion:gain (LysI:G), Cost:Gain (C:G), loin eye area (LEA), muscle depth (MD), first backfat layer (BF1), second backfat layer (BF2), total backfat (BFt), lean meat percentage, and carcass bonus index (BI). In phase I, there was a linear increase (P < 0.05) in FBW, ADG, NEI, and LysI with increasing NE levels in the diet. In phase II, increasing dietary NE levels also increased (P < 0.05) FBW, ADG, NEI, LysI, and FC linearly. Overall, there was a linear increase (P < 0.05) in ADG, NEI, LysI, and FC with increasing NE levels in the diet. The other performance variables were not affected (P > 0.05) by the NE levels. There was an increase (P < 0.05) in BF2 with increasing NE levels, but the other carcass characteristics were not altered (P > 0.05). We recommended 2.60 Mcal of NE kg-1 in the diet for growing barrows from 30 to 70 kg.